Studi Komparasi Pelet Buatan (Limbah Ikan dan Tanaman Kangkung) dan Pelat Buatan (Merk Takari) untuk Pengembangbiakan Ikan Ekor Pedang - Febry Ramadhani; Dea Sartika; Dinda Anisah Anisah; Rizka Lucy Nadia (LPPM IAI Nasional Laa Roiba Bogor, 2023)
This research was conducted to determine the differences in the types of feed, namely homemade pellets and pellets made by the takari brand which were given to the swordtail fish and then he observed the fish either through the behavior shown by the fish or the fish's response after being given the pellet feed. The method used is direct observation of the swordtail fish observed from day to day so it can be concluded that on homemade pellet feed fish are more aggressive in eating homemade pellets and also respond quickly to eat them quickly and devour while on takari brand pellet feed the fish eat it slowly and also the response takes a long time to eat it soit takes too long to finish. The dirt that is released by the swordtail fish is also a lot in general, fish, the swordtail fish eats a lot and also lots of dirt that comes out. Apart from looking at the type of food we also observe the reproductive system, the the respiratory and digestive systems are in good condition, there are no bad symptoms experienced by the swordtail fish in the reproductive system, in general, the reproduction of fish in other systemsis also fine, even the fish are healthy. Keywords: Homemade pellet feed, Fish response, Behavior, Swordtail fish reproduction